Using the WHO-AIMS to inform development of mental health systems: the case study of Makueni County, Kenya - Victoria N. Mutiso; Christine W. Musyimi; Isaiah Gitonga; Albert Tele; Romaisa Pervez; Tahilia J. Rebello; Kathleen M. Pike; David M. Ndetei (BMC, 2020)
Abstract Background In order to develop a context appropriate in mental health system, there is a need to document relevant existing resources and practices with a view of identifying existing gaps, challenges and opportunities at baseline for purposes of future monitoring and evaluation of emerging systems. The World Health Organization Assessments Instrument for Mental Health Systems (WHO-AIMS) was developed as a suitable tool for this purpose. Our overall objective of this study, around which research questions and specific aims were formulated, was to establish a baseline on mental health system as at the time of the study, at Makueni County in Kenya, using the WHO-AIMS. Methods To achieve our overall objective, answer our research questions and achieve specific aims, we conducted a mixed methods approach in which we did an audit of DHIS records and county official records, and conducted qualitative interviews with the various officers to establish the fidelity of the data according to their views. The records data was processed via the prescribed WHO-Aims 2.2 excel spreadsheet while the qualitative data was analyzed thematically. This was guided by the six domains stipulated in the WHO AIMS. Results We found that at the time point of the study, there were no operational governance, policy or administrative structures specific to mental health, despite recognition by the County Government of the importance of mental health. The identified interviewees and policy makers were cooperative and participatory in identifying the gaps, barriers and potential solutions to those barriers. The main barriers and gaps were human and financial resources and low prioritization of mental health in comparison to physical conditions. The solutions lay in bridging of the gaps and addressing the barriers. Conclusion There is a need to address the identified gaps and barriers and follow up on solutions suggested at the time of the study, if a functional mental health system is to be achieved at Makueni County.